Makna Kasih Sayang Keluarga dalam Film Korea - Ami Ainun Fahmi Rahmanda; Alex Sobur (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Minari’s film won the Oscar award with 6 consecutive nominations and a series of other awards in other competitions. This study used a qualitative research method with John Fiske's semiotic analysis approach. The purpose of this study was to determine the reality levels, representation, and ideology in Lee Isaac Chung's Minari film. The results of the study indicate that Minari Film is represented through appearance, speech, behavior, expression and environment, which is emphasized through shooting techniques. The values of the meaning of family affection are reflected in the environment, the place of shooting, appearance and costumes, movements and expressions, words, sentences, dialogues, photo propositions, shooting angles, and narration. Abstrak. Film Minari berhasil meraih penghargaan di piala Oscar dengan 6 nominasi berturut-turut dan sederet penghargaan lainnya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan analisis semiotika John Fiske. Tujuan dalam penelitian ini adalah untuk mengetahui level realitas, representasi, dan ideologi dalam film Minari karya Lee Isaac Chung. Hasil penelitian yang menunjukkan bahwa Film Minari direpresentasikan melalui penampilan, cara berbicara, perilaku, ekspresi dan lingkungan, yang dipertegas melalui teknik-teknik pengambilan gambar. Nilai-nilai makna kasih sayang keluarga tergambar melalui lingkungan, tempat pengambilan gambar, penampilan dan kostum, gerak dan ekspresi, kata, kalimat, dialog, proposisi foto, sudut pengambilan gambar, maupun narasi.